Integrating Discovery Learning and Deep Learning to Asses Critical Thinking and Problem Solving skill in Elementary Students - Mewa Zabeta; Ratnasari; Nikmah Nurvicalesti (Universitas Pendidikan Ganesha, 2026)
Low levels of students' critical thinking and problem solving skills remain a major challenge in mathematics learning, as instructional practices continue to emphasize rote memorization rather than providing sufficient opportunities for independent exploration. This study aimed to analyze students' critical thinking and problem solving skills through the implementation of Discovery Learning integrated with a Deep Learning approach. A quantitative descriptive research design was employed involving 25 fifth grade elementary school students. Data were collected through validated essay tests, classroom observations, and interviews, and were analyzed using descriptive statistics supported by qualitative data analysis. The findings revealed that students' critical thinking and problem solving skills were generally classified as moderate, with an overall achievement of 57%. In the critical thinking domain, the inference indicator achieved the highest score (63%), while in the problem solving domain, problem identification obtained the highest achievement (65%). The study concludes that integrating Discovery Learning with a Deep Learning approach effectively supports the development of students' critical thinking and problem solving skills by promoting active, exploratory, and student centered learning. These findings imply that the integration of both approaches can serve as an alternative instructional strategy to strengthen Higher Order Thinking Skills (HOTS) and numeracy literacy while providing practical guidance for teachers in designing more adaptive, contextual, and meaningful mathematics learning experiences at the elementary school level.